He's just not that into you [videorecording (DVD)]. - Affleck, Ben, 1972-; Barrymore, Drew; Aniston, Jennifer; Connelly, Jennifer; Johansson, Scarlett, 1984-; Long, Justin, 1978-; Goodwin, Ginnifer (New Line Video, 2009)
Tells the stories of a group of interconnected, Baltimore-based twenty- and thirtysomethings as they navigate their various relationships from the shallow end of the dating pool through the deep, murky waters of married life, trying to read the signs of the opposite sex...and hoping to be the exceptions to the 'no-exceptions' rule.